NILAI-NILAI KEKUASAAN DALAM UKIRAN RUMAH TUO DI KELURAHAN KAMPUNG BARUH KECAMATAN TABIR KABUPATEN MERANGIN - Mulia Jaya; Dwi Pradana Ariska (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
The values ​​of power possessed by traditional holders or ninik mamak in the Bungo Malay community can be seen from their position in the tuo house. Tuo's house is one of the cultural relics of ancient Malay, Jambi's house is synonymous with Old Malay customs. The method used in this research is a qualitative research method which is a case study. Research informants were selected by purposive sampling method. The results of the study found that the values ​​of power in the carving of the tuo house in Kampung Baruh Village, Tabir District, Merangin Regency, can be seen from the carvings on the tuo house ornaments, including: Carving of Keluk Paku (Pakis Wood) means that every development actor (leader) must be able to protect the The function and role it carries, Tampuk Manggis Carving means that the inner tribe shows politeness, sweet-faced hospitality to any guests who come. Carved Rope Philosophy of a strong bond and close kinship in the family, Carving Mensinding Gulung Paku (Pakis) showing the boundaries between mamak grandmothers, traditional elders, religious leaders with family and guest rooms, Carving Roots related to inner tribes if married their children from elements (matched) from their own family or from the same tribe. The efforts of the Merangin Regency Government in preserving the existence of tuo houses in Kampung Baruh Village, Tabir District, Merangin Regency, include making the area attractive, improving facilities and infrastructure and increasing accessibility.